1994
DOI: 10.4141/cjps94-095
|View full text |Cite
|
Sign up to set email alerts
|

Regrowth of smooth bromegrass (Bromus inermis Leyss.) following defoliation

Abstract: (Carlson and Newell 1983), and many producers are interested in using this forage in intensively managed grazing systems. However, information on the patterns of regrowth and rest periods required to achieve maximum regrowth following herbage removal is not well defined. This basic information is essential to the development of rotational grazing systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…As a result, Willson and Stubbendiek (2000) recommend avoiding burning areas where native warm-season grasses contribute less than 20% to the community. Regrowth of smooth brome following defoliation is reduced in dry years (Harrison and Romo 1994).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%
“…As a result, Willson and Stubbendiek (2000) recommend avoiding burning areas where native warm-season grasses contribute less than 20% to the community. Regrowth of smooth brome following defoliation is reduced in dry years (Harrison and Romo 1994).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%
“…Repeated defoliation beginning in the spring reduces vigor of plants (see Buwai and Trlica 1977;Lauenroth et al 1985;McLean and Wikeem 1985;Horton 1991;Willms 1991;Willms and Fraser 1992;Zhang and Romo 1994); other studies Harrison and Romo 1994;Romo et al 1995;Romo and Harrison 1999) have shown no adverse effects of a single defoliation on plant growth. In a similar light, greater reductions in plant growth occur when plants are defoliated later in the growing season or when dormant as compared to defoliation early in plant growth Harrison and Romo 1994;Romo et al 1995;Romo and Harrison 1999). In the present study, plants defoliated early in the growing season (May and June) either recovered their production potential sooner or at the same time as plants defoliated later in the growing season (July and August) or when dormant (September, October, November, and April).…”
Section: Discussionmentioning
confidence: 99%
“…Some plants in the Shortgrass Prairie of Colorado recover from defoliation in 14 to 26 mo, while other species require much longer rest periods . In the Northern Mixed Prairie of Saskatchewan, some plant species regain their production potential the year following defoliation (Harrison and Romo 1994;Romo et al 1995;Romo and Harrison 1999), yet growth of other plants is reduced for 1 to 2 yr (Romo et al 1995;Kowalenko and Romo 1998).…”
mentioning
confidence: 99%
“…In Utah, desert wheatgrass tillers emerge in late summer to autumn, they overwinter and resume growth the following spring (Mueller and Richards 1986;Olson and Richards 1988a). Northern wheatgrass produces tillers continuously through the growing season (Zhang and Romo 1994) whereas smooth bromegrass tillers in autumn and/or spring, depending on time of defoliation (Harrison and Romo 1994). In Saskatchewan, a cohort of crested wheatgrass tillers can emerge in autumn if temperatures are cool and if abundant precipitation is received (Romo pers.…”
Section: Discussionmentioning
confidence: 99%
“…Smooth bromegrass (Bromus inermis Leyss.) requires 1030-1180 GDD to reach maximum regrowth following defoliation (Harrison and Romo 1994). By comparison, northern wheatgrass (Agropyron dasystachyum [Hook.…”
mentioning
confidence: 99%